7D.11: RETINAL ARTERIOLAR STRUCTURE IN PATIENTS WITH PRIMARY ALDOSTERONISM. (June 2015) - Gosk-Przybylek, M.; Harazny, J.; Binczyk, E.; Szymanek, K.; Prejbisz, A.; Szaflik, J.; Kolodziejczyk-Kruk, S.; Pregowska-Chwala, B.; Makowiecka-Ciesla, M.; Janas, J.; Kadziela, J.; Warchol-Celinska, E.; et al.
Abstract : Objective: Since retinal arteriolar structure has not been evaluated in patients with secondary hypertension we addressed a question if retinal arteriolar structure in patients with primary aldosteronism (PA) is altered as compared with well-matched patients with essential hypertension (EHT). Figure. No caption available. Design and method: We examined 30 (18m/12f) patients with PA (54.1 ± 9.5 years) and 30 (18m/12f) age, gender, body mass index, glycemic status, blood pressure levels and number of medication (p > 0.05) matched patients (55.8 ± 8.4 years) with EHT. All patients with PA underwent adrenal venous sampling to differentiate between aldosterone producing adenoma (APA) and bilateral adrenal hyperplasia (BAH). Retinal microperfusion (RCF) and retinal arterioles' morphology were assessed by Heidelberg Retina Flowmetry using scanning laser Doppler flowmetry (SLDF). The parameters: outer diameter (AD) and lumen diameter (LD) were determined by automatic full-field perfusion imaging analysis (AFFPIA). Wall/lumen ratio (WLR), wall thickness (WT), and wall cross-sectional area (WCSA) were calculated. Results: Patients with PA were characterized by higher AD, WT, WLR and WCSA as compared with EHT (Table). There was no significant difference in LD, as well as in RCF between the groups (Table). Parameters describing retinal arterioles' morphology were not correlated to office and ambulatory blood pressure both in the PA group and in the EHT group. There was no significant difference in parameters describing retinal morphology between BAH and APA groups. Conclusions: Patients with primary aldosteronism as compared to matched hypertensive controls are characterized by higher outer wall diameter, wall thickness, wall-to-lumen ratio and wall cross sectional area of retinal arterioles reflecting hypertrophic vascular remodeling. This may indicate the detrimental effect of excessive aldosterone on small retinal arterioles evaluated non-invasively by SLDF method.